2014
DOI: 10.1149/2.017407jes
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characteristics of Electrochemical Reduction of SiO2Granules in Molten CaCl2

Abstract: The kinetic characteristics of electrochemical reduction of SiO 2 granules in molten CaCl 2 were investigated to develop a new process for producing solar-grade silicon. The reduction rate was evaluated based on the time dependence of the reduction fractions measured from the growth of the reduced Si layer and the weight change of the samples during electrolysis. The samples were prepared by potentiostatic electrolysis of SiO 2 granules in molten CaCl 2 at 1123 K. The results indicated that the reduction was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…In order to evaluate potential throughput of the process, we investigated the kinetic characteristics of the reduction process [22,23]. For this purpose, we used a small electrode consisted of a graphite crucible and an alumina tube [22] because it is convenient to conduct many experiments varying parameters, e.g.…”
Section: Direct Reduction Of Silica To Silicon Using Molten-salt Elecmentioning
confidence: 99%
“…In order to evaluate potential throughput of the process, we investigated the kinetic characteristics of the reduction process [22,23]. For this purpose, we used a small electrode consisted of a graphite crucible and an alumina tube [22] because it is convenient to conduct many experiments varying parameters, e.g.…”
Section: Direct Reduction Of Silica To Silicon Using Molten-salt Elecmentioning
confidence: 99%
“…Electrochemical reduction of solid oxides in molten salt has been widely studied since it was firstly reported by Fray and his colleagues. [49][50][51][52][53][54][55][56][57] We originally demonstrated that solid silica (SiO 2 ) can be electrochemically reduced to solid Si in molten salts via the solid-to-solid reaction: [58][59][60][61][62][63][64][65][66][67][68][69][70][71] SiO 2 (s) + 4e -→ Si (s) + 2O 2-(1)…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of solar-grade silicon by the electrochemical reduction of solid SiO 2 in molten CaCl 2 has been studied for many years [11][12][13][14]. The electrochemical reduction process of SiO 2 to Si was proposed to proceed through the dynamic conductor/insulator/electrolyte three-phase interline mechanism [15].…”
Section: Introductionmentioning
confidence: 99%